Griffiths-like phase close to the Mott transition - Mello, Isys F. [UNESP]; Squillante, Lucas [UNESP]; Gomes, Gabriel O.; Seridonio, Antonio C. [UNESP]; Souza, Mariano de [UNESP] (Amer Inst Physics, 2020)
We explore the coexistence region in the vicinity of the Mott critical end point employing a compressible cell spin- 1 / 2 Ising-like model. We analyze the case for the spin-liquid candidate kappa-(BEDT-TTF) 2Cu 2(CN) 3, where close to the Mott critical end point metallic puddles coexist with an insulating ferroelectric phase. Our results are fourfold: (i) a universal divergent-like behavior of the Gruneisen parameter upon crossing the first-order transition line; (ii) based on scaling arguments, we show that within the coexistence region, for any system close to the critical point, the relaxation-time is entropy-dependent; (iii) we propose the electric Gruneisen parameter Gamma E, which quantifies the electrocaloric effect; and (iv) we identify the metallic/insulating coexistence region as an electronic Griffiths-like phase. Our findings suggest that Gamma E governs the dielectric response close to the critical point and that an electronic Griffiths-like phase emerges in the coexistence region.